As aventuras de Antoine Doinel: síntese do estilo de direção de François Truffaut - Guilherme Marcilio Penido Amaral (2022)
This dissertation proposes the analysis of the five films that make up what is called “Antoine Doinel's Adventures”, produced between 1959 and 1979, considered here as a synthesis of François Truffaut's (1932-1984) cinematographic direction style. The research was carried out through analyzes that seek to validate this proposition, examining the influence of filmmakers such as Jean Renoir, Ernst Lubitsch, Alfred Hitchcock, among others, in the conception, mise en scène and in the way Truffaut directed his films; and investigating how the autobiography and the use of the concept of “Author Politics” in a practical way by Truffaut in his films became the main narrative strategies in the construction of his directing style. To this end, studies on style by David Bordwell (2013) were used, as well as testimonies and musings by François Truffaut himself (1989; 2004; 2005), both in his texts and in the work of Antoine De Baecque and Serge Toubiana (1998) and Anne Gillain (1990), whose statements certify the hypotheses addressed in this research.